Case Report: A case of immune hemolytic anemia after liver transplantation: passenger lymphocyte syndrome is the culprit - Zhao, Qianzhe (Frontiers in Transplantation, 2024)
Passenger lymphocyte syndrome (PLS) is most commonly observed after solid organ transplantation with minor ABO blood group incompatibility. It consists of a set of clinical symptoms brought on by the remaining lymphocytes of the donor organ developing antibodies against the recipient's antigens. Here, we describe a typical case of PLS in a type A+ recipient receiving a liver transplant from a type O+ donor. She suffered from jaundice, abnormally decreased hemoglobin level, and severe hemolytic anemia without bleeding. During hemolysis, we detected a positive direct antiglobulin test (DAT), and the thermal elution test revealed the presence of IgG anti-A antibodies in her serum. When immunosuppressive agents and blood transfusion were used together, cross-matched O+ washing red blood cells led to an expected outcome without side effects.